Management Of Patients With Anxiety And Dental Fear - Diana Cerghizan; Monica Balos; Carmen Biris; Liana Hantoiu (Romanian Society of Oral Rehabilitation, 2009)
Oral rehabilitation treatment is often challenging if the patient has dental fear and anxiety. The purpose of this study is to observe the extent of behavioral management on dental anxiety and fear. It is based on two questionnaires to assess dental fear and anxiety Dental Fear Survey (DFS) and Modified Dental Anxiety Scale (MDAS). Based on these questionnaires was selected a group of patients with medium and high dental fear and anxiety. In oral rehabilitation treatment was applied a treatment protocol specifically developed for people with dental fear and anxiety. After finishing the treatments we reapplied the questionnaires aiming to see how have changed level of dental anxiety and fear. The results show a lower level of fear and anxiety in patients with medium fear and anxiety (test of significance Wicoxon p